Analysis of students’ science process skills in low plant botany online learning through telegram - Yudhistian, Yudhistian; Wulandari, Tabitha Sri Hartati (STKIP Persada Khatulistiwa Sintang, 2025)
Research that discusses and examines the role of Telegram in developing science process skills (SPS) in low plant botany (LPB) learning in depth is still minimal. Therefore, the research aims to determine the level of SPS of students in LPB online learning through Telegram. The research method used a quantitative descriptive study of students' SPS levels after LPB learning through Telegram. The research was conducted with 60 students, using a questionnaire as the research instrument, followed by quantitative analysis. Results showed that students had a deep understanding and an adequate level of SPS in LPB online learning through Telegram, as evidenced by the average SPS score of 72.91% in the high category. Thus, Telegram has been proven to help develop students' SPS in LPB online learning. The study provides implications for educators by utilizing Telegram as a platform for online learning methods to develop students' SPS skills.